THE INTERSECTIONS OF BODY AND SPACE IN LILLIAN HELLMAN’S THE CHILDREN’S HOUR - Özlem Karagöz Gümüşçubuk (Toplum ve Kültür Araştırmaları Dergisi)
The intention of this article is to analyze Lillian Hellman’s play The Children’s Hour (1934) in terms of the intersections of body and space. For this reason, this play has previously been analyzed in terms of feminism and sexual identities, but this article proposes to bring a new perspective concentrating on theories of both the body and space. For this purpose, this article attempts to reveal how public space and private space coincide with each other and reveal that sexual identities can also be socially constructed.